If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 16 + -20x = 40 Reorder the terms: 16 + 12x + -20x = 40 Combine like terms: 12x + -20x = -8x 16 + -8x = 40 Solving 16 + -8x = 40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -8x = 40 + -16 Combine like terms: 16 + -16 = 0 0 + -8x = 40 + -16 -8x = 40 + -16 Combine like terms: 40 + -16 = 24 -8x = 24 Divide each side by '-8'. x = -3 Simplifying x = -3
| 49b^2+64=0 | | 9m^2=100 | | 4y+x=7 | | 5w^2+12=-8 | | 5x-6y+5a= | | 2(x-3)-3(x-1)=5 | | 8=3+5(y-2) | | 3x+4+35x+68+2x=56 | | 0.04(4t+8)=0.16(t-5)+1.12 | | 7x^2=-21x | | 7(n+1)-4n=4 | | -3(y+7)=2(-2y-8) | | w=p(y-z) | | 8-(4y-4)=2-5y | | 7x^2+18x+8=0 | | x+1.4=7.3 | | 3+2(2v-1)=2(3v-8)+4v | | 2x^2-25+21=0 | | 2x^2-5x+24=0 | | 4x^2-5x+21=0 | | -(2x-5)-(2x-5)+4=-4(x-1)-(4x+5)+3 | | 2x^2-5x+21=0 | | 16(n+6)=4(24+4n) | | 2v-1+2(2v+5)=-3(v-1) | | 2x^3-3x^2-11x+6=0 | | 4(u-2)-8=-5(-3u+8) | | 4(3+u)-u=6+3(u+2) | | -3(w+5)+5w=2(w-6) | | 3(x-2)+5=2(3x-5) | | 5y-10=15x | | 4(u-2)-3u=2(u-6) | | 3(2+y)-y=6+2(y+1) |